THE EFFECT OF MOTIVATION FOR THE PREVENTION OF CORRUPTION ACTS IN THE MINISTRY OF INTERNAL AFFAIRS - Todorova, Irena (Annals of Spiru Haret University. Economic Series, 2022)
The report presents the objective need for motivation as an element of managerial impact in the Ministry of Internal Affairs. The activity of the state administration should correspond to the high public expectations for professional competence, legality, integrity, correctness and responsibility. That is why motivation is the key element that leads to the formation of specific behavior aimed at the observance of value orientations in the performance of official duties and is an important prerequisite for the prevention of corrupt behavior among the employees of the Ministry of Internal Affairs.